IMPLEMENTATION OF DESIGN THINKING TECHNOLOGY IN THE TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS - Tiahur , Vasyl (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article discusses the issue of introducing design thinking technology into the training of future primary school teachers, which will contribute to the development of creativity, initiative, the expansion of project-technological, research activities, to form the ability to generate new ideas and initiatives, to organize work with students in this direction, stimulating them to design thinking.